Development and validation of modules improving self-awareness excellent services of academic staff - Taufik, Taufik; Fadli, Rima Pratiwi; Putri, Yola Eka (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2019)
This research is begun based a purpose to increasing self-awareness of education personnel, so they can perform an excellent service for students in the university. This study aims to: (1) describe the module design to increase self-awareness of excellent service of education personnel (2) perform module validation tests and (3) perform module reliability tests. The study was descriptive involving four experts and 12 education staff at Padang State University as the subject of the trial. Instruments used to include (1) Validity Testing Instruments Module Contents (2) Ifdil & Taufik Self-Awareness Inventory and (3) Module Instruments. The results of this study reveal that the Self-Awareness Improvement Module for Excellent Services Education Personnel can be accepted and can be used for self-awareness programs for the staff in providing services.